2011
DOI: 10.4999/uhod.10060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grape seed Extract and Origanum Onites Essential Oil on Cisplatin-Induced Hepatotoxicity in Rats

Abstract: Cisplatin is a widely used anticancer drug but, it can produce undesirable effects such as hepatotoxicity even in therapeutic doses. The underlying mechanism in hepatotoxicity has been attributed to free oxygen radicals. The present study was designed to determine the possible protective effects of grape seed extract (GSE) and Origanum onites essential oil (OOEO) on liver toxicity induced by cisplatin. Ninetysix-male Wistar albino rats were divided into eight groups, twelve in each (Control, GSE, OOEO, GSE+OOE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…However, the CP + Propolis and CP + NP application significantly changed this difference in a positive way ( Table 2 ). In a study conducted on rats with liver damage induced by CP, Cetin et al [ 50 ] investigated the effects of grape seed and essential thyme oil on some serum blood parameters. They determined that CP caused a statistically significant increase in serum ALT and AST levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the CP + Propolis and CP + NP application significantly changed this difference in a positive way ( Table 2 ). In a study conducted on rats with liver damage induced by CP, Cetin et al [ 50 ] investigated the effects of grape seed and essential thyme oil on some serum blood parameters. They determined that CP caused a statistically significant increase in serum ALT and AST levels.…”
Section: Discussionmentioning
confidence: 99%
“…Caffeic acid phenethyl ester (CAPE), one of the main ingredients of propolis, blocks the production of ROS [ 60 ]. The results of previous studies reported that CP caused damage in the liver tissue by increasing the MDA level and decreasing antioxidant enzymes; however, antioxidant contributions minimized that damage [ 50 , 61 ]. In a study using grape seed extract to determine whether or not especially effective phenolic compounds could reduce liver damage [ 50 ], it was found that superoxide dismutase and GSPx activities in the liver tissue were significantly higher in the CP + grape seed extract group compared to the CP alone.…”
Section: Discussionmentioning
confidence: 99%
“…According to Opitz Peñuelas and Llusiá (2002) stated that temperature increases the emission and production rates of most terpenes and can replace photorespiration of the plant in protection from photodamage by scavenging oxygen-reactive species; likely explaining our observations in this study. Abdelhafiz et al (2014), Cetin et al (2011) and Dkhil et al (2013) and stated that using a plant-derived-material can protect against cisplatin-induced hepatotoxicity. P. minus is one of those candidate plants due to high level of FIGURE 5.…”
Section: Discussionmentioning
confidence: 99%
“…El-Sayyad et al (2009) and Kart et al (2010) showed that cisplatin induced severe anomalies in liver tissue histology and the ultrastructure. Whilst the mechanisms underlying cisplatin-induced hepatoxicity remains poorly understood, oxidative stress is thought to primarily mediate cisplatininduced hepatotoxicity (Cetin et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Some endemic Origanum species including O. acutidens are used as herbal teas in the regions where they grow (Tumen et al, 1995). In addition, Origanum species are widely used as culinary herbs, in alcoholic beverages and to flavor food products (Aligiannis et al, 2001;Bendahou et al, 2009;Cetin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%